Cinema 4D R18 Essential Training: Motion Graphics. - Needham, Andy (linkedin.com, 2016)
Learn how to use CINEMA 4D R18 in a motion graphics workflow. Learn key foundational concepts, such as spline modeling, keyframe animation, and materials.